2019
DOI: 10.1152/jn.00555.2018
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and behavioral reactivity to social exclusion: a functional infrared thermal imaging study in patients with psoriasis

Abstract: Recent studies have shown that sympathetic nervous system (SNS) activity can be heavily impacted not only by basic threats to survival but also by threats to social bonds. In this study we explored the behavioral and physiological consequences of social exclusion/inclusion in patients with psoriasis, a disease frequently associated with the experience of being ostracized and with deficient emotion regulation skills. We employed a virtual ball-tossing game (Cyberball) to induce the experience of social exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 83 publications
2
15
0
6
Order By: Relevance
“…Two subscales of the DERS, namely, emotional clarity and emotion acceptance, which are believed to measure concepts that are very close to alexithymia, also show higher scores among these patients (Innamorati et al, 2016). In agreement, in two recent studies, we showed that psoriasis patients scored higher than controls in the "Lack of Emotional Clarity" subscale of the DERS, indicating that patients have more difficulties than controls in correctly identifying their own emotions (Panasiti et al, 2019;Ponsi et al, 2019).…”
Section: Emotion Regulationsupporting
confidence: 89%
See 2 more Smart Citations
“…Two subscales of the DERS, namely, emotional clarity and emotion acceptance, which are believed to measure concepts that are very close to alexithymia, also show higher scores among these patients (Innamorati et al, 2016). In agreement, in two recent studies, we showed that psoriasis patients scored higher than controls in the "Lack of Emotional Clarity" subscale of the DERS, indicating that patients have more difficulties than controls in correctly identifying their own emotions (Panasiti et al, 2019;Ponsi et al, 2019).…”
Section: Emotion Regulationsupporting
confidence: 89%
“…Our review also highlights some limitations of the approaches that have been used so far for studying emotional processes in psoriasis. First of all, only few studies (Mastrolonardo et al, 2006(Mastrolonardo et al, , 2007van Beugen et al, 2016;Panasiti et al, 2019;Ponsi et al, 2019) reported behavioral and physiological evidence. Although we acknowledge that self-report measures are important to understand the conscious evaluation that patients have of themselves, we also believe that implicit measures are crucial to understand what are the abilities that are truly compromised in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, researchers have found shortened sleep duration and worse sleep quality to be influenced by the exposure to such factors the following day ( 20 , 42 ). Studies show that the feeling of social isolation is associated with increased secretion of pro-inflammatory cytokines as well as pro-inflammatory gene expression and alterations in hormone signaling, similar to what we observe after sleep deprivation ( 4 , 28 , 43 ). Research has also revealed that social isolation may independently trigger health-damaging behaviors, for instance, smoking and alcohol abuse, which are mentioned above as contributing to sleep deprivation ( 38 ).…”
Section: Negative Effects Of Decreased Quality Of Life and Psychoemotional And Socioeconomic Burden On Sleep Qualitysupporting
confidence: 84%
“…The invested money is multiplied by three and then the trustees can decide whether to return half of the sum to the investors or to keep for themselves the entire amount. People tend to trust more their in-group vs. out-group (i.e., parochial trust), and are strongly influenced by the information regarding the reputation of the trustee (Boero, Bravo, Castellani, & Squazzoni, 2009;Ponsi, Monachesi, Panasiti, Aglioti, & Panasiti, 2019) with the lowest trust directed to strangers (i.e., people defined by non-diagnostic information, De Dreu, 2018). We hypothesized that the expectation of reciprocity (i.e., the idea that others reciprocate our generosity) would play a role in UCB donation.…”
mentioning
confidence: 99%